Comparison of toric intraocular lens tilt and decentration measurement using dynamic Purkinje-meter and anterior segment optical coherence tomography - Palkovicova, Eliska; Cendelin, Jiri; Novak, Jiri (Biomedical papers, 2025)
Aims. To present a new method of dynamic Purkinje-metry and to verify it by comparison with a commercially available anterior segment optical coherence tomography CASIA2. Patients and Methods. A dynamic Purkinje-meter with a movable fixation target was assembled. A coaxial circular pattern formed by infrared LEDs was projected onto the eye and evoked Purkinje images (1st, 3rd, 4th = P1, P3, P4). The measurement was performed on 29 eyes with an implanted toric IOL (intraocular lens), under mydriatic conditions, with reference to the visual axis. The IOL tilt was calculated from the position of a fixation target at the moment of P3 and P4 superposition. The IOL decentration was determined based on the relative position of P1 during on-axis fixation and of P3 and P4 superposition during off-axis fixation. A custom-developed software was used for distance measurements. Using CASIA2, the IOL position was fully calculated by the device. Results. The mean absolute difference between CASIA2 and Purkinje-meter values was 0.6° extpm 0.4° for the tilt magnitude and 10° extpm 10° for the tilt direction, and 0.11 mm extpm 0.08 mm for the decentration magnitude and 16° extpm 14° for the decentration direction. There was no statistically significant difference between the values determined by the two methods for the tilt and decentration direction. The differences were statistically significant for the tilt and decentration magnitude. Conclusion. The values of IOL tilt and decentration direction are similar for both devices. The values of IOL tilt and decentration magnitude measured by Purkinje-meter are higher than those from CASIA2, but overall, they correspond to the values presented in other published studies.
Keywords: intraocular lens position; intraocular lens decentration; intraocular lens tilt; Purkinje images; anterior segment optical coherence tomography; CASIA2